EXPLORING THE IMPACT OF SOCIOLINGUISTICS IN ENGLISH LANGUAGE TEACHING - Axmedova Gulbahor Abduvali qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: In this article, scientists’ theoretical concepts and case studies were analyzed related to the importance of sociolinguistic factors in English language teaching. Multiple recommendations, methods and teaching techniques were suggested to teach target learners effectively and efficiently.